2001
DOI: 10.1073/pnas.221381098
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nitrite rather than nitrate reflects regional endothelial nitric oxide synthase activity but lacks intrinsic vasodilator action

Abstract: The plasma level of NOx, i.e., the sum of NO2 ؊ and NO3 ؊ , is frequently used to assess NO bioavailability in vivo. However, little is known about the kinetics of NO conversion to these metabolites under physiological conditions. Moreover, plasma nitrite recently has been proposed to represent a delivery source for intravascular NO. We therefore sought to investigate in humans whether changes in NO x concentration are a reliable marker for endothelial NO production and whether physiological concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
395
5
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(434 citation statements)
references
References 45 publications
18
395
5
11
Order By: Relevance
“…There is evidence to suggest that the plasma [nitrite] sensitively reflects endothelial nitric oxide synthase activity [32] and that L-citrulline supplementation can increase nitric oxide synthase activation [20] and nitric oxide biomarkers [19,21]. [nitrite]) were increased after 4 weeks supplementation with watermelon pomace in Zucker diabetic fatty rats [31], but the current study is the first, to our knowledge, to suggest that watermelon juice supplementation can increase nitric oxide production through nitric oxide synthase in humans.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…There is evidence to suggest that the plasma [nitrite] sensitively reflects endothelial nitric oxide synthase activity [32] and that L-citrulline supplementation can increase nitric oxide synthase activation [20] and nitric oxide biomarkers [19,21]. [nitrite]) were increased after 4 weeks supplementation with watermelon pomace in Zucker diabetic fatty rats [31], but the current study is the first, to our knowledge, to suggest that watermelon juice supplementation can increase nitric oxide production through nitric oxide synthase in humans.…”
Section: Discussionmentioning
confidence: 53%
“…Consequently, watermelon juice ingestion has been reported to increase plasma L-citrulline [29] and L-arginine [29,30], and may also increase nitric oxide biomarkers [31]. We recently reported that seven days of supplementation with 6 g Lcitrulline·day -1 tended to, but did not significantly, increase plasma [nitrite] [22], a sensitive marker of nitric oxide synthase activity [32]. It has been suggested that concurrently supplementing with L-citrulline and glutathione is more effective at increasing plasma nitric oxide markers than L-citrulline alone [33].…”
Section: Introductionmentioning
confidence: 92%
“…Furchgott and Bhadrakom in 1953 used supraphysiological concentrations of acidified nitrite to relax precontracted aortic strips (148). The idea that nitrite is an in vivo regulator of vascular tone was challenged years later when it was reported that physiological concentrations of nitrite are insufficient to regulate vascular tone (149). However, nitrite is now thought to serve as a source of · NO under pathophysiological conditions such as hypoxia and ischemia where NOS derived · NO is unavailable.…”
Section: <28>mentioning
confidence: 99%
“…Instead, serum nitrite, a metabolite, is measured as a qualitative marker of NO release. The same increased values of serum nitrite in the nanomole range that occur with increased shear stress during flow-mediated dilation or aerobic exercise do not produce immediate vasodilatation when infused into the circulation at such concentrations in humans (30,44,47). Therefore, in this investigation, we relied on the vasodilator properties of NO to assess effectiveness of pG z .…”
mentioning
confidence: 97%